DNMT3a Downregulation Ttriggered Upregulation of GABAA Receptor in the mPFC Promotes Paclitaxel‐Induced Pain and Anxiety in Male Mice - Lixia Tian; Xu‐Hui Li; Yu‐Long Zhao; Hui‐Yuan Yi; Xue‐Ru Liu; Rongrong Yao; Xue‐Mei Hou; Xuan Zhu; Fu‐Quan Huo; Tao Chen; Lingli Liang (Advanced Science)
Abstract Chemotherapeutic agents, such as paclitaxel (PTX), induce neuroplastic changes and alter gene expression in the prefrontal cortex (PFC), which may be associated with chemotherapy‐induced pain and negative emotions. Notably, DNA methylation undergoes adaptive changes in neurological disorders, emerging as a promising target for neuromodulation. In this study, systemic administration of PTX leads to a decrease in the expression of the DNA methyltransferase DNMT3a, while concurrently upregulating the expression of Gabrb1 mRNA and its encoded GABAARβ1 protein in the medial PFC (mPFC) of male mice. Overexpression of DNMT3a in the mPFC alleviates PTX‐induced pain hypersensitivity, and anxiety‐like behavior in these mice. Additionally, it reverses the PTX‐induced increase in inhibitory synaptic transmission in the pyramidal neurons of the mPFC. Mechanistically, the upregulation of GABAARβ1 in the mPFC is linked to the reduced expression of DNMT3a and DNA hypomethylation at the promoter region of the Gabrb1 gene. Furthermore, a long‐term diet rich in methyl donors alleviates PTX‐induced pain hypersensitivity and anxiety‐like behavior in mice. These findings suggest that the DNMT3a‐mediated upregulation of GABAARβ1 in the mPFC contributes to PTX‐induced neuropathic pain and anxiety, highlighting DNA methylation‐dependent epigenetic regulation as a potential therapeutic target for addressing chemotherapy‐induced cortical dysfunction.